Relationship of Entrepreneurial Orientation and Managerial Skills Among Co-Operative Managers in Sabah and Sarawak - Stanley Tan; Noor Fzlinda Fabeil; Bonaventure Boniface; Geoffrey Harvey Tanakinjal; Stephen Laison Sondoh Jr. (RMP Publications, 2022)
Co-operatives continue to dominate Malaysia's socio-economic system, as evidenced by the number of co-operatives in existence. Malaysia claimed around 14,000 co-operatives in 2019. Co-operatives' contribution to the economy was little, and they failed to meet the National Co-operative Policy's objectives (NCP). A lack of cash, activity, structure, management, governance and poor networking have plagued Malaysian co-ops. It is a mess because of bad management and violation of the Act and related laws. Despite the NCP's heavy backing for Malaysian co-operatives, the enterprises have not been as successful as predicted. The Resource-Based View (RBV) theory examines an organization's resources, both tangible and intangible. The current study focuses on intangible human capital, specifically the entrepreneurial orientation (EO) of co-operative firms and managerial skills (MS). For this study, co-operative managers in Sabah and Sarawak were asked about their entrepreneurial attitudes, managerial skills, and company success. The inquiry paradigm will be postpositivist. Because of this, the current study uses multidimensional constructs for management skills but tests each of them separately to see how EO influences the six dimensions. The resource-based approach (RBV) is theoretically based on a prospective paradigm that has aroused controversy among scholars from three research orientations. So, utilizing RBV theory to assess multidimensional managerial talents seems appropriate for this study. The study is quantitative and relies on questionnaire responses from Sabah and Sarawak residents. The research tool was pre-tested before delivering the final questionnaire. This study used 500 sets of questionnaires, with 288 returned. This study only included co-operatives that have been operating for three years or more to measure business success. Purposive sampling was used to collect data from Sabah and Sarawak co-operatives. Statistical analysis of 244 usable questionnaires. SmartPLS 3.3.3 examined the links between entrepreneurial orientation (EO) and Managerial Skills (MS). The results suggest that entrepreneurial orientation (EO) improves financial, network, marketing, human resource management, organizing, and strategic planning skills. The results suggested that co-operative managers should look to entrepreneurial orientations to improve their management skills and contribute to prosperity.